Digital Problems and Parental Support among Thai Learners during Online Learning - Flores, Anna Mae A; Espinosa, Cherilyn F; Tadle, Vicar Loren (ASEAN Multidisciplinary Research Journal, 2021)
In April 2021, the 3rd wave of the covid-19 pandemic hit the whole country of Thailand. The majority of the schools decided to change from face-to-face learning to online learning. The abrupt closure of schools is mandated, and students are missing the time for playing with friends, social interaction for learning and development, and their daily routine of discipline in school. Parents automatically became vital learning agents at home, facilitating and assisting students in understanding how to continue learning, how to use digital tools, and how to maintain and support students in this manner. This study was a design of the parental support at home, the technicalities using distance learning of the parents and teachers, and other accessible online avenues. This qualitative method was purposely to explore and investigate further the experiences of parents, students, and teachers about distance learning and management during the Covid-19 pandemic era to obtain valuable insight and understanding of real-life experiences in varying situations and circumstances. A purposive sampling technique was used for data collection. Data were collected from seventy (70) Primary Thai parents and thirty-six (36) foreign teachers falling in the inclusion criteria. Considering the COVID-19 restrictions, the data were collected via Google Forms and online interviews. The analysis of the obtained data focused on two (2) themes: (A) The digital problems encountered by Thai parents and foreign teachers during online learning and (B) The influence of Thai parents on their children’s academics during online learning. The findings of this study highlighted the areas in digital technology that Thai parents and foreign teachers found difficulties during online learning. Internet connection and lack of knowledge on using platforms were found to be the top problems among foreign teachers. The same problem was found among parents; having and giving all the other things concerning juggling around may help parents and children develop a sense of solidarity and comfort. The undertaking may seem overwhelming and daunting because families are experiencing pressures with additional financial stress and employment flux. However, the findings on the influence of parents on students during online learning were promising. Parents believe that their involvement at home responsibility is needed and significant. Among the good parental practices were expecting their children to do well in online learning and following up their children’s classwork by asking what they had learned.